Answer:
= 30.67°F
≅ 30.70°F
Step-by-step explanation:
Newton's law,
![T(t) = T_(s)+(T_(0) + T_(s))e^(-kt)](https://img.qammunity.org/2021/formulas/physics/high-school/gibky0335sm9tbergcrl79j6i8xixml9l8.png)
When T(t) is the final temperature
= Temperature of surrounding
= Initial temperature
=duration of cooling
k = constant
![46 = 0+(155-0)e^(-k* 15)46 = 155e^(-15k)](https://img.qammunity.org/2021/formulas/physics/high-school/ooxhir9tomncn6gd5nqzwhstj8ub21yrvb.png)
Now take natural log on both the sides
![ln(46)=ln(155e^(-15k))ln(46)=ln(155)+ln(e^(-15k))ln(46)=ln(155)=-15k\\3.8286 - 5.0434 = -15k](https://img.qammunity.org/2021/formulas/physics/high-school/6da03g4i6uuiyx2oobg1t3agxh4zpa52t2.png)
k = 0.081
![T(t)=0+(155-0)e^((0.081* 20))](https://img.qammunity.org/2021/formulas/physics/high-school/kge6h3viiwuv3yso2o9gfgg7peop7ppfiw.png)
![= 155e^(-1.62)](https://img.qammunity.org/2021/formulas/physics/high-school/960bevv7uq538nr3b6an2buxi0o1s8ppm5.png)
= 155 (0.1979)
= 30.67°F
≅ 30.70°F